Implementing Emergency Cash Transfers : The Philippine Experience in Response to the 2016/17 Disasters - Acosta, Pablo; Palma, Pam; Perez, Joedie; Velarde, Rashiel (World Bank, Washington, DC, 2018)
Around the globe, there is an unending cycle of producing innovative policies that are relevantand responsive to today's complex problems of disaster risk reduction and mitigation. A lot ofevidence is pointing to the shifting paradigm in responding to emergencies. Foremost amongthem is the growing acceptance of cash transfers as a response tool to disasters.The Philippines is not oblivious to this developing paradigm. The Philippines is considered tohave one of the most advanced social protection (SP) systems in the East Asia Pacific region.These SP systems are designed to help poor households manage risk and shocks. Currently,there are different types of cash transfers being used by the Department of Social Welfare andDevelopment (DSWD) programs. These include: (1) the Pantawid Pamilya conditional cashtransfer (CCT) program; (2) the Sustainable Livelihood Program (SLP) using cash-for-work; and,(3) the National Community Driven Development program (NCDD). These programs use variousmodalities and mechanism for cash transfers in different stages of the post-disaster timeline.However, the SP element of DSWD's disaster risk management and response interventions canbe significantly improved especially if to be used as a response tool during disasters.